P817 Symptoms of COVID-19 in Patients with Immune Mediated Inflammatory Diseases. (30th January 2023) - Schlosser, T; Krasselt, M; Elsing, L; Hecker, M; Holler, B; Hoffmeister, A
Abstract: Background: Pandemic situation of the novel coronavirus disease (COVID-19) represents a challenging condition with a plethora of aspects. Symptoms of patients with immune mediated inflammatory diseases (IMID) such as inflammatory bowel disease (IBD) and different rheumatic diseases are not well described. Methods: We conducted a prospective questionnaire-based study (04/2022 – 10/2022) at our university medical center. Outward patients over the age of 18 years were screened. Participating patients reported about their individual COVID-19 history during pandemic′s course. Results: In the end, 156 patients were willing to participate. Vast majority of the cohort had an established diagnosis of inflammatory bowel disease (117 [75%] vs. 39 [25%] patients with rheumatic disease). Eightyone patients (51%) self-reported about their COVID-19 infection. Diagnosis had usually been established by positive PCR. In general, courses of infection were mild: Only two patients (2% of patients with reported COVID-19) were hospitalized due to COVID-19 with one of the two needing intensive care. Asymptomatic COVID-19 had been described by 7 persons (9% of patients with reported COVID-19). Acute COVID-19 was accompanied by fatigue/tiredness in 58 persons (72% of patients with COVID-19) as most frequent symptom. Other complaints were common cold (55 patients = 68%), cough (51 patients = 63%), headache (44 patients = 54%) and fever (35 patients = 43%). Joint respectively muscle pain was a symptom of eight respectively nine patients with rheumatic IMID (=33%/38% of 24 self-reported COVID-19). Five rheumatic patients (21%) presented diarrhea as complaint due to COVID-19. In the IBD subgroup 15 patients (27% of 57 self-reported COVID-19) had this complaint. Painful joints were mentioned in 23 IBD patients (41%). Aching muscles occurred in 19 IBD patients (34%). Conclusion: Discrimination between symptoms of COVID-19 in contrast to chronic IMID condition can be difficult as complaints might be overlapping.